Nucleic-Acid-Binding Chromophores as Efficient Indicators of Aptamer-Target Interactions - Sarpong, Kwabena; Datta, Bhaskar (Journal of Nucleic Acids, 2012)
The binding affinity and specificity of nucleic acid aptamers have made them valuable candidates for use as sensors in diagnostic applications. In particular, chromophore-functionalized aptamers offer a relatively simple format for detection and quantification of target molecules. We describe the use of nucleic-acid-staining reagents as an effective tool for detecting and signaling aptamer-target interactions. Aptamers varying in size and structure and targeting a range of molecules have been used in conjunction with commercially available chromophores to indicate and quantify the presence of cognate targets with high sensitivity and selectivity. Our assay precludes the covalent modification of nucleic acids and relies on the differential fluorescence signal of chromophores when complexed with aptamers with or without their cognate target. We also evaluate factors that are critical for the stability of the complex between the aptamer and chromophore in presence or absence of target molecules. Our results indicate the possibility of controlling those factors to enhance the sensitivity of target detection by the aptamers used in such assays.